Sebaran Frekuensi dan Pola Distribusi Lola (Trochus niloticus Linnaeus, 1767) di Perairan Pulau Lemukutan dan Pulau Penata Besar Kalimantan Barat - Panggabean, Grin Tommy (Dept. Marine Science, 2026)
Lemukutan and Penata Besar Islands located in Bengkayang Regency, are characterized by coral reef formations and relatively clear waters that meet the ecological requirements for the natural habitat of the lola snail, Trochus niloticus. This study aimed to analyze the size–frequency distribution and spatial distribution pattern of T. niloticus in the waters of Lemukutan and Penata Besar Islands. Sampling was conducted using the belt transect method (50 m × 4 m) at four stations: Tanjung Jati, Penata Besar, Tanjung Batu Bedaon, and Melanau Timur (Batu Kapal). A total of 67 individuals were recorded during the study, consisting of 12 individuals (17.91%) at Tanjung Jati, 15 individuals (22.39%) at Penata Besar, 27 individuals (40.30%) at Tanjung Batu Bedaon, and 13 individuals (19.40%) at Melanau Timur (Batu Kapal). The population was dominated by individuals in the size classes of 8.5–9.1 cm and 9.1–9.7 cm, representing 34% of the total observations, indicating a predominance of medium-sized individuals. Spatial distribution analysis using the Morisita Index revealed a clumped distribution pattern (Id > 1) at Penata Besar, Tanjung Batu Bedaon, and Melanau Timur (Batu Kapal). In contrast, the population at Tanjung Jati exhibited a random distribution pattern (Id = 0.86). These findings provide baseline ecological information to support sustainable management and conservation strategies for T. niloticus in the study area.